Diagnostik holistik pasien faringitis dengan hipertensi di Puskesmas Bahu (Jurnal Kedokteran Komunitas dan Tropik, 2022)
Pharyngitis is one of the most common diseases that occurs in most people. This report is a case discussionÂ  of a 67-year-old man with painful swallowing, cough, and chills. The patient has a smoking habit, and has a history of hypertension, with a regular antihypertensive drug consumption, such as amlodipine. This discussion is related to a holistic diagnostic approach to the patient's complaints, in order to better understand the factors associated with the occurrence of the disease in the patient.Keywords: pharyngitis, hypertension, holistic diagnosticÂ